2020
DOI: 10.3390/polym12040835
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Almond Shell Waste on Physicochemical Properties of Polyester-Based Biocomposites

Abstract: Polyester-based biocomposites containing INZEA F2® biopolymer and almond shell powder (ASP) at 10 and 25 wt % contents with and without two different compatibilizers, maleinized linseed oil and Joncryl ADR 4400®, were prepared by melt blending in an extruder, followed by injection molding. The effect of fine (125–250 m) and coarse (500–1000 m) milling sizes of ASP was also evaluated. An improvement in elastic modulus was observed with the addition of< both fine and coarse ASP at 25 wt %. The addition of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
7
12
0
2
Order By: Relevance
“…Figure 6 c,d shows the DSC thermograms obtained during the DSC cooling and second heating scans for all formulations. Two different peaks were observed for neat INZEA, indicating the presence of two main polyesters in the polymer matrix, in agreement with the behavior previously observed by Ramos et al [ 58 ]. The analysis of the experimental curves indicated that no substantial variations were introduced in the glass transition temperatures, while the main effect was related to the shift of melting and crystallization temperatures, in parallel with the evidence or disappearance of multiple melting peaks.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 6 c,d shows the DSC thermograms obtained during the DSC cooling and second heating scans for all formulations. Two different peaks were observed for neat INZEA, indicating the presence of two main polyesters in the polymer matrix, in agreement with the behavior previously observed by Ramos et al [ 58 ]. The analysis of the experimental curves indicated that no substantial variations were introduced in the glass transition temperatures, while the main effect was related to the shift of melting and crystallization temperatures, in parallel with the evidence or disappearance of multiple melting peaks.…”
Section: Resultssupporting
confidence: 91%
“…In particular, the curves related to mass loss (a) and derivative weight loss (b) for the system containing 7 wt% of nanopigments (representative of the same trend observed for the formulations containing 3 and 5 wt% of nanopigments) are reported in Figure 6 a,b. As it has been reported [ 58 ], a double degradation peak can be found for the INZEA neat matrix, with two main steps centered at 350 and 400 °C, that could match with the possible degradation temperatures of PLA and poly(butylene succinate) (PBS) polyesters, respectively. It is also important to note that at 900 °C, unmodified INZEA matrix maintained a residual mass of ca.…”
Section: Resultssupporting
confidence: 75%
“…5 wt% at 900 • C, which was increased when the nanofillers were introduced. This behaviour is in accordance with the possible presence of an inorganic filler in the formulation of the commercial product, as it has been reported in other work [62].…”
Section: Thermal Stabilitysupporting
confidence: 92%
“…Although the main academic focus of biodegradable polymer reinforcement in recent years has been on the use of organic natural fillers [18][19][20], the use of inorganic mineral fillers such as talc [21,22], calcium carbonate [23,24], kaolin [25,26], and mica [27,28] and their impact on the biodegradability of these polymers [29][30][31] has been investigated as well. As the properties of particulate polymer composites can highly fluctuate strongly, due to variations in additional polymer additives, processing techniques, and the applied test methods, it is generally complex to compare individually reported results [32][33][34]. Therefore, this work is a comparative study on the effect of various particulate fillers (talc, calcium carbonate, kaolinite, mica) on the most important mechanical properties of a selected number of industrially available biodegradable polymers (PBS, PBSA, PHBH, and PBAT) while keeping all other factors constant.…”
Section: Introductionmentioning
confidence: 99%